A18 Indirect pathway linage-specific alterations from early development in Huntington's disease. (12th September 2022) - Vila, Cristina; Londoño, Francisco J; Esteve-Codina, Anna; Molina-Ruiz, Francisco J; Canals, Josep M
Abstract : Huntington's disease (HD) is a currently incurable neurodegenerative disorder that manifests itself through motor and cognitive symptoms due to a predominant loss of striatal medium spiny projection neurons (MSNs) in the striatum. Although HD is a neurodegenerative disease, growing evidence show that developmental alterations could be a key factor in the disease, determining the future vulnerability of certain cell types, such as striatal MSNs. Here we show an early HD-related expression pattern elucidated by bulk and 10X single cell RNA-seq performed on control and HD isolated striatal primordia at different developmental stages in the mouse model zQ175. Transcriptomic data together with histological analyses allowed us to characterize crucial developmental events occurring in HD. We found that early alterations in cell cycle progression and cell fate determination in HD embryos give rise to an imbalance between specific neural precursor cells and neurons, affecting specifically the indirect MSNs (iMSNs) linage generation. Moreover, iMSNs undergo specific apoptosis postnatally in HD. Development finally ends up with a reduction of the iMSNs population inhabiting the adult striatum in HD. Developmental alterations can set the stage for the HD-specific vulnerability of iMSNs and basal ganglia homeostasis loss. Identifying and modulating candidate pathways or genes is crucial to develop new strategies to restore neuronal homeostasis and protect striatal MSNs halting disease progression. This work has been supported by Ministerio de Ciencia, Innovación y Universidades; ISCIII-Subdirección General de Evaluación and European Regional Development Fund (ERDF) [RETICS]; Catalonia Trade and Investment, Generalitat de Catalunya; and La Caixa Foundation, Spain; CHDI foundation Inc, USA; and European Commission, Europe.